Propositions to marketers' relationship effectiveness in cross-border mergers and acquisition integration contexts - Jedin, Mohd. Haniff (2011)
Research on marketing integration related to mergers and acquisitions (M&A) has paid little attention to the combination of similar resources between two similar departments, particularly in the cross-border M&A context. Furthermore, exixting research does not clearly demonstrate the role of relationship among marketers' within the amalgamation process between acquirer and target firm. Hence, this paper addresses few propositions that related to strengthening the relationship effectiveness among the marketers in both firms, which at the same time upload the M&A performance. Collaboration and interaction are proposed as drivers to increase optimistic relationship among marketers. Drawing from the extent literature, propositions are developed, elaborating success factors to improve M&A integration performance.